The Opportunity for a Sustainable Social Economy in Vacant Spain: An Empirical Analysis in COVID-19 Confinement - Natividad Buceta-Albillos; Esperanza Ayuga-Téllez (Urban Science)
The COVID-19 pandemic offers an opportunity for the revitalisation of empty Spain and the development of new sustainable business models in a healthier environment, taking the competitive advantages of digitalisation and the benefits of contact with nature. This study presents a positive analysis of the situation after three months of confinement with the research objective of evaluating the potential for development a sustainable social economy in empty Spain based on the hypotheses presented. In order to demonstrate the six hypotheses put forward in the research, a review of the existing literature was conducted, socio-economic and environmental indicators from official sources were consulted, and descriptive statistics methods have been applied. Digitalisation, the social economy, the bio-economy, and the revitalisation of heritage seem to be the drivers for achieving the challenges proposed. By perceiving reality through a lens that values nature and creative intelligence, a new avenue of opportunities may be opened up, leading to an improvement in quality of life and well-being, and potentially retaining the rural population. Following this study, which assesses the opportunities, risks, and challenges and establishes a plan of measures, players, and resources for future implementation in vacant Spain, new lines of work will become available.